Comparative Study On The Current And Potential Commercial Utilisation Of Motion Capture Versus Keyframe Animation - Zainal Abidin, Mohamad Izani (2003)
The demand of 3D digital animation production nowadays had led animators and producers not to limit to only keyframe animation but other tools and technologies. Amongst the key factors in determining such tools may refer to content, data accuracy, sampling rate, the freedom of motion, flexibility, skill sets required and cost. This research provides a comprehensive study on two animation techniques namely keyframe animation and motion -capture.